PENGGUNAAN MEDIA PEMBELAJARAN EDMODO DALAM MENINGKATKAN HASIL BELAJAR PAI DI SEKOLAH MENENGAH PERTAMA NEGERI 2 KARAWANG BARAT - Alvian Muhamad Fadhilah; Abu Bakar; Ilham Fahmi (Universitas Islam Madura, 2023)
The Covid-19 pandemic has changed all aspects of human life, including in the world of education, which requires adjustments to environmental situations and conditions, starting from elements of learning material, methods of delivering material, and implementation which was previously carried out face-to-face, must now be changed. to a remote system. Even though schools are closed, online learning is an alternative way to carry out learning activities in educational implementation. This then results in low student learning outcomes in PAI subjects. This is one of the motives for researchers to conduct research related to the research theme. This research uses the Classroom Action Research method. Each cycle includes two learning meetings and one daily repeat test. This research was conducted on 30 student subjects from SMPN 2 West Karawang. The research results showed that the average learning outcomes of students in the sufficient category were 77.07, while the learning outcomes of students in the good category in cycle II rose to 86.10. This shows that the use of Edmodo learning media can improve PAI learning outcomes for students. The implication of this research is as evaluation material and additional reference for teachers and all education practitioners. Improving learning outcomes can be done by implementing learning methods that are attractive to students, which in this case is the Edmodo learning media.